2001
DOI: 10.1039/b008502m
|View full text |Cite
|
Sign up to set email alerts
|

Late transition metal complexes of a new P–N ligand Ph2PCH2N(H)C5H3(Cl-5)N: synthesis and structural studies

Abstract: N pyridyl complexes were characterised by a combination of multinuclear NMR, IR spectroscopy and elemental analyses. Furthermore the crystal structures of 5È7 and 12 have been determined and reveal several types of NÈHÉ É ÉX (X \ N, F or Cl ; inter-or intra-molecular) hydrogen bonding contacts. The structure of 12 represents an extremely rare, crystallographically characterised, MÈPÈCÈNÈCÈN six-membered metallacyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…We have previously found that Mannich based condensation reactions are extremely facile for the syntheses of functionalised tertiary and ditertiary phosphines [29][30][31][32][33][34]. Carboxylic acid phosphines [32,34] can be prepared by this procedure and furthermore, we have shown some of these ligands serve as convenient building blocks for the preparation of linear, dinuclear gold(I) complexes [35] with unusual finite and infinite structures.…”
Section: Synthesis and Characterisationmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously found that Mannich based condensation reactions are extremely facile for the syntheses of functionalised tertiary and ditertiary phosphines [29][30][31][32][33][34]. Carboxylic acid phosphines [32,34] can be prepared by this procedure and furthermore, we have shown some of these ligands serve as convenient building blocks for the preparation of linear, dinuclear gold(I) complexes [35] with unusual finite and infinite structures.…”
Section: Synthesis and Characterisationmentioning
confidence: 96%
“…We are unaware of any systematic studies exploring the supramolecular chemistry of RuCl 2 (p-cymene)(PR 3 ) with phosphines from a similar ligand library. As part of ongoing studies in our group [29][30][31][32][33][34][35] we have used Mannich-based condensation reactions as an excellent procedure for synthesising highly functionalised tertiary and ditertiary phosphines. Herein we describe the use of isomeric, carboxylic acid or mixed phenol/carboxylic acid containing tertiary phosphines, Ph 2 PCH 2 Y, for the preparation of a range of RuCl 2 (p-cymene)(Ph 2 PCH 2 Y) complexes.…”
mentioning
confidence: 99%
“…1) occupies a special position of 1 site symmetry. In (I), the tertiary phosphine oxide has a distorted tetrahedral geometry with a P O bond length of 1.483 (3) Å , which is consistent with appreciable double-bond character (Coles et al, 2001).…”
Section: Commentmentioning
confidence: 78%
“…Some of them have rigid back bond and some other have flexible alkyl chain that join the two/three donor atoms. Moreover, few complexes of Fe, Au, Ag and W with diphenyl-2-pyridylphosphine and 4-(dimethylamino)phenyldiphenylphosphine ligands have also been reported [20][21][22][23]. Our interest in the present work is to extend the boundary-line of the phosphinoamine chemistry towards 1 st row transition metals and herein we report the synthesis of Co(II) complexes with 4-(dimethylamino)phenyldiphenylphosphine and diphenyl-2-pyridylphosphine ligands and characterization of these complexes.…”
Section: Introductionmentioning
confidence: 93%